Situational Strategic Planning in primary care: troubleshooting and reinventing actions - Ariane Graças de Campos (Universidade de Fortaleza, 2009)
Objective: To apply the Strategic Situational Planning (SSP) in a problem selected by the Family Health team, aiming at proposing intervention strategies to correct this deficiency. Methods: A field research of quantitative nature, applied in a family health unit of a town in the countryside of São Paulo state, using the steps of SSP in the period from April to October, 2008. Results: The selected problem was that of underreporting of production in the unit, thereby undermining the efficiency of obtaining positive results regarding the access, effectiveness of the strategies and changes in the context of health in the coverage area. After intervention with the team focusing awareness on the importance of maintaining updated data and information on the population served, it understood the importance of formalizing all procedures performed in the Unit. Conclusion: The Strategic Situational Planning brought to light the relevance in learning more about the community of which the unit is responsible, its complexity and heterogeneity, making effective the quality of rendered services, linking them to the recovery of professional activities and of the health service as a whole.